Answers

  • Brainly User
2015-11-13T22:53:43+08:00
Let the first integer be x
Second integer be x + 1
Product of the two integers = 42

Equation:
(x) (x + 1) = 42
x² + x = 42

Transform to quadratic equation, ax² + x -42 = 0
x² + x - 42 = 0

Solve by factoring:
(x + 7) (x - 6) = 0

x + 7 = 0                 x - 6 = 0
x = -7                      x = 6

Choose the positive root, x = 6

The two consecutive integers:
First integer: x ⇒   6
Second integer: x + 1 = 6 + 1       ⇒   7

The two consecutive integers are 6 and 7.

Check:
(6) (7) = 42
42 = 42
0
thank you,,, very much momgie... =)))
You're welcome:-)